'Despite Circumstance': The Principles of Medical Ethics and the Role of Hope. Issue 3 (2nd September 2018) - Westin, Anna
Abstract : In this paper, I will examine how the role of hope can inform our interpretation of the classical principles of medical ethics. Defining hope as a future-oriented expectation for the good, I will look at how it can shape our understanding of justice, beneficence, respect for autonomy and non-maleficence. I will suggest that ethically engaging with these principles in medical practice requires placing value on the patient–practitioner relation as a mode of hope. Engaging the writings of Emmanuel Lévinas and Søren Kierkegaard, I will show how hope reveals itself through responsible and expectant relationship, even in the midst of suffering.